Faktor-Faktor Yang Berhubungan Dengan Pemanfaatan Voluntary Counselling and Testing (VCT) Pada Ibu Hamil di Wilayah Kerja Puskesmas Karanganyar Kota Tasikmalaya - Dudi Ahmad M; Sri Mulyanti; Neni Nuraeni (STIKes Karsa Husada Garut, 2019)
Human Immunodeficiency Virus (HIV) is a condition where a person does not have immunity. The disease can be transmitted from pregnant women to the child they are carrying, in an effort to detect early HIV, VCT needs to be done. Karanganyar Community Health Center data in 2017 VCT service coverage for pregnant women in 2017 was less than 26.7%. This study aims to determine the factors associated with the use of VCT in pregnant women. This type of research is quantitative by using descriptive correlation method and cross sectional approach. The population is 70 pregnant women who were obtained by purposive sampling technique. Data obtained by closed questionnaire and data analyzed using frequency distribution and chi square test. The results showed knowledge about VCT examination included less (52.9%), attitudes included negative (55.7%), secondary education (52.9%), most did not work (67.1%), more than half received less support from their husbands (57.1%), and most did not utilize VCT services (72.9%). Factors related to the use of VCT are knowledge (p value 0,000), attitude (p value 0,000), education (p value 0,000) and husband's support (p value 0,000), unrelated factors are work (p value 0.196). The conclusion from this study factors related to the use of VCT are knowledge, attitudes, education and husband's support. Therefore, it is better for health workers, especially nurses, to provide nursing services to pregnant women, especially the use of VCT services as an effort in early detection of HIV in pregnant women. Keywords: Factors, Utilization of VCT Services